1985
DOI: 10.1002/j.2161-1920.1985.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Employment and Job Satisfaction of Vietnamese Refugees

Abstract: Vietnamese refugees reporting job satisfaction have been in the United States longer and are more proficient in speaking English than dissatisfied refugees, but they are not more positive about job-seeking resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Tang and O"Brien concluded that refugees would focus on attaining vocational goals that were in line with their self-concepts once they acclimated to the present culture. Similarly, other researchers have found that acculturation and length of time in the United States were related to job satisfaction (Anh & Healy, 1985;Leong, 2001). In summary, there were significant positive relationships found between time in the United States and employment status and satisfaction.…”
Section: Although Park and Harrison Found No Between Group Differencesupporting
confidence: 58%
“…Tang and O"Brien concluded that refugees would focus on attaining vocational goals that were in line with their self-concepts once they acclimated to the present culture. Similarly, other researchers have found that acculturation and length of time in the United States were related to job satisfaction (Anh & Healy, 1985;Leong, 2001). In summary, there were significant positive relationships found between time in the United States and employment status and satisfaction.…”
Section: Although Park and Harrison Found No Between Group Differencesupporting
confidence: 58%
“…While the causal relationship between mental health and English acquisition remains unclear, refugees' generally poorer English skills place them at a disadvantage in the labor market and, ultimately, in securing self-sufficiency (Wooden, 1991). The association between English acquisition and selfsufficiency has been identified in a number of studies (Anh & Healy, 1985;Westermeyer et al, 1990;Tran, 1992).…”
Section: Language Acquisitionmentioning
confidence: 99%